Benthic injury dose–response models for polychlorinated biphenyl–contaminated sediment using equilibrium partitioning. (13th December 2016) - Finkelstein, Kenneth; Beckvar, Nancy; Dillon, Tom
Abstract: The study goal was to develop a sediment polychlorinated biphenyl (PCB) dose–response model based on benthic invertebrate effects to PCBs. The authors used an equilibrium partitioning (EqP) approach to generate predicted PCB sediment effect concentrations (largely Aroclor 1254) associated with a gradient of toxic effects in benthic organisms from effects observed in aquatic toxicity studies. The present study differs from all other EqP collective sediment investigations in that the authors examined a common dose–response gradient of effects for PCBs rather than a single, protective value. The authors reviewed the chronic aquatic toxicity literature to identify measured aqueous PCB concentrations and associated benthic invertebrate effects. The authors control‐normalized the aquatic toxic effect data and expressed results from various studies as a common metric, percent injury. Then, they calculated organic carbon–normalized sediment PCB concentrations (mg/kg organic carbon) from the aqueous PCB toxicity data set using EqP theory based on the US Environmental Protection Agency's (EPIWEB 4.1) derivation of the water–organic carbon partition coefficient ( K OC ). Lastly, the authors constructed a nonlinear dose–response numerical model for these synoptic sediment PCB concentrations and biological effects: Y  = 100/1 + 10 ([logEC50–log X ] × [Hill slope]) (EC50 = median effective concentration). These models were used to generate "look‐up" tables reporting percent injury in benthic biota for a range of Aroclor‐specific sediment concentrations. For example, the model using the EPIWEB K OC estimate predicts mean benthic injury of 23.3%, 46.0%, 70.6%, 87.1%, and 95% for hypothetical sediment concentrations of 1 mg/kg, 2 mg/kg, 4 mg/kg, 8 mg/kg, and 16 mg/kg dry weight of Aroclor 1254, respectively (at 1% organic carbon). The authors recommend the model presented for screening but suggest, when possible, determining a site‐specific K OC that, along with the tables and equations, allows users to create their own protective dose–response sediment concentration. Environ Toxicol Chem 2017;36:1311–1329. © 2016 SETAC